An Integrated Framework for Financial Positions and Flowson a From-Whom-To-Whom Basis : Concepts, Status, and Prospects - Fassler, Segismundo (IMF Working Papers; Working Paper, 2012)
The global crisis of 2008 highlighted the need to understand financial interconnectedness among the various sectors of an economy and between them and their counterparties in the rest of the world. However, application of this kind of analysis has been hampered by the lack of adequate data. This paper sets the background for promoting internationally coordinated efforts for compiling and disseminating data on sectoral financial positions and flows on a from-whom-to-whom basis within the framework of the System of National Accounts. It draws on actual experiences in compiling these kinds of data and provides guidelines for their development in the future.